Business rules in knowledge management and in information systems – methodology of mining business rules and knowledge - Ivana Rábová; Michal Hodinka (Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis, 2011)
Every organisation works according to principles which define business logic that controls all business processes. However, lot of basic rules of business logic are hidden in companies’ guidelines and directives, in informal techniques of experts, processes owners and specialists. The aim of all managers should be a replacement of this incoherent set of information by set of clear and unambiguous terms which describe the way the company is controlled from inside. This notion is a ground of control and administration of business knowledge.Contemporary practises in development of informational systems demand openness and availability to correspond to constant changes. With the complexity of information system grows the amount of work and its level of difficulty. The rules of business logic are transferred to application logic and implemented into a source code. Therefore, change of the business rule needs change of the code. This means compilation or replacement of the code. Adoption of this new approach would mean more effective possibilities in adjustment of the information systems to environment dynamics thanks to the change of the rules. The article deals with mining methods and subsequent structure of business rules for easier implementation into information system. Business rules base is at the same time business knowledge base which can serve for different purposes then development and use of information systems.